Vasiliy Ivanovich Perveyev (to 70th birthday) - m. editor (Бюллетень сибирской медицины, 2012)
The creative biography of Professor V.I. Perveyev, prominent Russian scientist, head of Traumatology, Orthopedy and Field Surgery Chair of Siberian State Medical University is presented. The main trends of scientific and public activity are concerned.